The longitudinal impact of psychological flexibility and compassion on mother-baby bonding: Care4mmmies study protocol [comunicação oral] - Mateus, Vera (2023)
Becoming a mother is a life-changing event that is often experienced in a positive way, but may also encompass great vulnerability and uncertainty, with the potential to hinder the mother’s well-being and foster disorganization, particularly for women with attachment difficulties dealing with a difficult infant. Risk factors to the quality of mother-infant emotional bonding are well documented, whereas research into the mothers’ protective and modifiable factors is scarcer. Psychological flexibility and compassion are adaptive emotional regulation strategies that have been linked to the wellbeing and mental health in diverse populations. The current work intends to present the Care4mommies project, which aims to examine whether prenatal maternal compassion (towards others and the self) and psychological flexibility play a protective role in the development of postpartum mother-infant bonding over time and whether this effect remains relevant regardless of mothers’ attachment style and infant temperament. Participants will be pregnant women to be assessed between 22 and 30 weeks of gestation (T0) and when the infant is three (T1) and nine months old (T2). Participants will respond to an online survey that includes sociodemographic information and questionnaires about their compassion and psychological flexibility to be completed at all three assessments. In addition, mothers’ own attachment style will be reported during pregnancy, and infant temperament and mother-infant bonding questionnaires will be administered at T1 and T2. Recruitment will take place through social media advertising, colleagues and acquaintances of the research team members, and family health units attending pregnant women. Data will be analysed using a structural equation modelling approach. Overall, we expect that higher levels of mother’s compassion and psychological flexibility will predict higher quality of mother-infant bonding. In addition, we expect that the impact of less adaptive maternal attachment styles and infant difficult temperament on mother-infant bonding will be moderated by mother’s compassion and/or psychological flexibility. Finally, we expect mother-infant bonding at T2 to be predicted by mothers’ attachment style, compassion and psychological flexibility, infant temperament, and mother-infant bonding previously assessed. The study findings will clarify whether mothers’ compassion and psychological flexibility may be protective for mother-infant bonding, which can inform future studies in designing and testing specific parental interventions to promote a secure mother-infant bond in the postpartum period.